Urgensi Pendidikan STEM Terhadap Literasi Sains Mahasiswa Calon Guru Sekolah Dasar - Yuyu Yuliati; Dudu Suhandi Saputra (International Consortium of Education and Culture Research Studies, 2019)
Education has a very central role in building quality human resources in order to survive and live life in a global era full of competition, so we need a pattern of science learning that is oriented to the paradigm of technology-based learning. Science, Technology, Engineering, And Mathematics learning is one of learning that is able to develop the competencies of students to solve problems faced in everyday life through the use of technology. Since the role of teachers in education is very important, preservice teachers of primay school must have a deep knowledge of science. In other words, preservice teachers of primay school must have good scientific literacy. scientific literacy is one of the important aspects that must be mastered by preservice teachers of primay school, because it influences the learning process in elementary school. scientific literacy is very important to solve various problems related to ethics, morals and global issues due to rapid changes in the fields of science and technology.